Pelatihan dan Pendampingan Pencatatan Keuangan Pada Persatuan Wanita Patra Pertamina Fuel Terminal Badas Sumbawa - Agus Wahyudi; Ayu Levia Tryana; Jayanti Mandasari; Fahlia (Adi Widya : Jurnal Pengabdian Masyarakat, 2022)
Financial records are the main problem faced by business actors, especially micro, small and medium enterprises. So that the service team of the Faculty of Economics and Business, University of Technology, Sumbawa, provides training and financial records for micro, small and medium business actors for mothers who already have businesses who join the Patra Pertamina Fuel Terminal Badas Sumbawa Women's Union. The method applied to this service is to provide training and assistance related to financial recording and provide assistance in the use of the Si Apik application (Financial information recording application system). The result of this service is that the training participants have obtained basic knowledge of financial records in accordance with standards that have never been done so far. Mentoring is carried out to train data input to prepare financial reports. This service has achieved the expected results and this program continues to be carried out with a mentoring pattern.